To solve the equation 8/9(x + 1/2) = 32/3 for x, we can start by simplifying the left side of the equation.
First, distribute the 8/9 to both terms inside the parentheses:
(8/9)(x) + (8/9)(1/2) = 32/3
This becomes:
8x/9 + 4/9 = 32/3
Next, combine the fractions on the left side:
(8x + 4) / 9 = 32/3
To solve for x, we can cross multiply:
3(8x + 4) = 32(9)
Multiply both sides of the equation:
24x + 12 = 288
Next, isolate the term with x:
24x = 288 - 12
24x = 276
Finally, divide both sides by 24 to solve for x:
x = 276/24
Simplifying the fraction 276/24:
x = 23/2
Therefore, the solution for x is x = 23/2.
what is the solution of the equation 8 / 9 ( x + 1/2 ) equals 32 / 3 when solving for X (1 point)
3 answers
8/9(x + 1/2) = 32/3
8 (x+1/2) = 3 * 32 = 96
x + 1/2 = 12
z = 11 1/2
8 (x+1/2) = 3 * 32 = 96
x + 1/2 = 12
z = 11 1/2
Apologies for the previous response, there appears to be a mistake. Let's go through the solution again:
To solve the equation (8/9)(x + 1/2) = 32/3 for x, follow these steps:
Step 1: Distribute the 8/9 to the terms inside the parentheses.
(8/9)(x) + (8/9)(1/2) = 32/3
This simplifies to:
8/9 * x + 4/9 = 32/3
Step 2: Multiply both sides of the equation by the reciprocal of 8/9, which is 9/8, to eliminate the fraction.
(9/8)(8/9 * x + 4/9) = (9/8)(32/3)
This simplifies to:
x + (9/8)(4/9) = (9/8)(32/3)
Step 3: Simplify both sides of the equation.
x + 4/8 = 12/1
This can be further simplified to:
x + 1/2 = 12
Step 4: To solve for x, subtract 1/2 from both sides.
x + 1/2 - 1/2 = 12 - 1/2
This simplifies to:
x = 11 1/2
Therefore, the solution for x in the equation (8/9)(x + 1/2) = 32/3 is x = 11 1/2 or x = 23/2.
To solve the equation (8/9)(x + 1/2) = 32/3 for x, follow these steps:
Step 1: Distribute the 8/9 to the terms inside the parentheses.
(8/9)(x) + (8/9)(1/2) = 32/3
This simplifies to:
8/9 * x + 4/9 = 32/3
Step 2: Multiply both sides of the equation by the reciprocal of 8/9, which is 9/8, to eliminate the fraction.
(9/8)(8/9 * x + 4/9) = (9/8)(32/3)
This simplifies to:
x + (9/8)(4/9) = (9/8)(32/3)
Step 3: Simplify both sides of the equation.
x + 4/8 = 12/1
This can be further simplified to:
x + 1/2 = 12
Step 4: To solve for x, subtract 1/2 from both sides.
x + 1/2 - 1/2 = 12 - 1/2
This simplifies to:
x = 11 1/2
Therefore, the solution for x in the equation (8/9)(x + 1/2) = 32/3 is x = 11 1/2 or x = 23/2.